A two‐stage model predictive control with zero‐sequence voltage injection for a three‐level T‐type inverter - Yechun Xin; Yanxu Wang; Gang Wu; Shouqi Jiang; Weiru Wang; Chaobin Wang; Wei Wang (IET Power Electronics, 2021)
Abstract Three‐level inverter systems based on the conventional Finite Control Set‐Model Predictive Control (FCS‐MPC) principle are characterized by large current ripples, difficult‐to‐design weighting factors and variable switching frequencies. In order to solve these problems, in this study a two‐stage model predictive control is proposed that consists of two objective functions: the current prediction and neutral point potential prediction objective functions. The first objective function was based on the mathematical model of a three‐level T‐type, and the second was based on the zero‐sequence injection principle and intended to modify the modulated signals. Then, a multi‐carrier modulation method was adopted to attain the switching signal for the inverter system. In addition, this paper analyses the sensitivity of the inductance and load resistance parameters for the predictive model. Finally, the performance of the proposed strategy is evaluated based on the time‐domain simulation and experiment study.